Overexpression of the RieskeFeS protein increasese electron transport rates and biomass yield - Simkin, Andrew J.; McAusland, Lorna; Lawson, Tracy; Raines, Christine A. (American Society of Plant Biologists, 2017)
In this study, we generated transgenic Arabidopsis (Arabidopsis thaliana) plants overexpressing the Rieske FeS protein (PetC), a component of the cytochrome b6f (cyt b6f) complex. Increasing the levels of this protein resulted in concomitant increases in the levels of cyt f (PetA) and cyt b6 (PetB), core proteins of the cyt b6f complex. Interestingly, an increase in the levels of proteins in both the photosystem I (PSI) and PSII complexes also was seen in the Rieske FeS overexpression plants. Although the mechanisms leading to these changes remain to be identified, the transgenic plants presented here provide novel tools to explore this. Importantly, overexpression of the Rieske FeS protein resulted in substantial and significant impacts on the quantum efficiency of PSI and PSII,electron transport, biomass, and seed yield in Arabidopsis plants. These results demonstrate the potential for manipulating electron transport processes to increase crop productivity.